2005
DOI: 10.1124/mol.105.016741
|View full text |Cite
|
Sign up to set email alerts
|

Drug Binding Interactions in the Inner Cavity of hERG Channels: Molecular Insights from Structure-Activity Relationships of Clofilium and Ibutilide Analogs

Abstract: Block of human ether-a-go-go related gene (hERG) Kϩ channels by otherwise useful drugs is the most common cause of long QT syndrome, a disorder of cardiac repolarization that predisposes patients to potentially fatal arrhythmias. This undesirable long QT side effect has been a major reason for the withdrawal of medications from the pharmaceutical market. Understanding the molecular basis of hERG block is therefore essential to facilitate the design of safe drugs. Binding sites for hERG blockers have been mappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 37 publications
(40 reference statements)
5
103
2
Order By: Relevance
“…It is a recurring condition for the K v 11.1 channel [encoded by the human ether‐à‐go‐go‐related gene (hERG) also called KCNH2 ], which, together with its β‐subunit MinK‐related peptide 1, is responsible for I Kr . Key aromatic residues in the S6 helix (Tyr 652 , Phe 656 ) and the pore helix (Thr 623 , Ser 624 , Val 625 ) of the K v 11.1 channel have been identified as the detrimental target of a broad spectrum of compounds (Perry, 2005) that impair K + ion flux through the pore and therefore reduce I Kr . This generates a prolongation of the QT interval of the electrocardiogram (ECG), with the potential occurrence of a polymorphic form of ventricular tachycardia known as torsades de pointes (TdP), which can cause sudden death (Sanguinetti and Tristani‐Firouzi, 2006).…”
Section: Cardiotoxicity Caused By Electrical Disruptionmentioning
confidence: 99%
“…It is a recurring condition for the K v 11.1 channel [encoded by the human ether‐à‐go‐go‐related gene (hERG) also called KCNH2 ], which, together with its β‐subunit MinK‐related peptide 1, is responsible for I Kr . Key aromatic residues in the S6 helix (Tyr 652 , Phe 656 ) and the pore helix (Thr 623 , Ser 624 , Val 625 ) of the K v 11.1 channel have been identified as the detrimental target of a broad spectrum of compounds (Perry, 2005) that impair K + ion flux through the pore and therefore reduce I Kr . This generates a prolongation of the QT interval of the electrocardiogram (ECG), with the potential occurrence of a polymorphic form of ventricular tachycardia known as torsades de pointes (TdP), which can cause sudden death (Sanguinetti and Tristani‐Firouzi, 2006).…”
Section: Cardiotoxicity Caused By Electrical Disruptionmentioning
confidence: 99%
“…A closed conformation state model of hERG has been also used as a template for docking studies [45,99]. By rotating the S6 helix of the closed conformation model, Perry et al (2006) [45] suggested that most compounds position along the ion conduction pathway and that the geometrical arrangement of features are in good agreement with pharmacophore distribution predicted by a ligand-based approach [17].…”
Section: In Silico Prediction Systems For Chemical Block Of Hergmentioning
confidence: 65%
“…By rotating the S6 helix of the closed conformation model, Perry et al (2006) [45] suggested that most compounds position along the ion conduction pathway and that the geometrical arrangement of features are in good agreement with pharmacophore distribution predicted by a ligand-based approach [17]. MK-499 was reported to be retained in the central cavity, and hERG was in the closed state [100].…”
Section: In Silico Prediction Systems For Chemical Block Of Hergmentioning
confidence: 73%
See 1 more Smart Citation
“…Most HERG-blocking drugs that have been examined for their molecular determinants of blockade have been shown to be dependent on a variety of amino-acid residues in the pore-S6 region (the inner lining of the pore). Alanine-scanning mutagenesis has previously been used to determine residues important for block of the HERG channel (5,26), which showed that drug-induced blockade was dependent on a variety of amino-acid residues in the S6 helices. Presumably, the residues of S6 that face into the vestibule and those residues deep in the selectivity filter might trap drugs within the vestibule and contribute to their efficacy of block.…”
Section: Molecular Determinants Of Herg-channel Block By Procainementioning
confidence: 99%